The Issue of Which Municipality Belongs to the Taxes on the Ships Operated in the Euphrates River - Gündüz, Ahmet (Fırat University, 2020)
In the Ottoman Empire, land, sea and river routes carried out transportation and communication services. At the crossroads of highways and rivers, transpor-tation was provided either by making bridges or by ships operated on the piers established.Transportation was provided through many boats operated on the Euphrates River within the Mamuretü'l-aziz province. The transportation was carried out with-out delay by the boats operated on the piers located in the isolation and Herdi districts of Harput on the middle road starting from Istanbul to Baghdad.These boats are also important sources of income for the municipalities they are affiliated with. Taxes of Izoli and Herdi boats (rüsum) were managed by the municipality of Malatya from Tanzimat until the 1890s. However, since one side of the river was in the central province administration (Mamuretü'l-aziz), half of these revenues had to be left to the administration of the central province municipality. For this purpose, the Provincial Administration Council made a decision and requ-ested the correction of this situation.In this study, it will be tried to clarify whether the isolation of Isoli and Herdi boats belongs to Malatya municipality or the provincial central municipality Mamu-retü'l-aziz within the framework of the data in the documents in the Ottoman Archive Department ŞD-1494-23.

Osmanlı Devletinde ulaşım ve haberleşme hizmetleri kara, deniz ve nehir yollarıyla gerçekleştiriliyordu. Karayolları ile nehirlerin kesiştiği noktalarda ya köprüler yapılarak ya da kurulan iskelelerde işletilen gemiler vasıtası ile ulaşım sağlanıyordu. Mamuretü’l-aziz vilayeti dâhilinde, Fırat nehri üzerinde işletilen birçok kayık sayesinde ulaşım sağlanmaktaydı. İstanbul’dan başlayarak Bağdat’a giden orta yol üzerinde bulunan Harput’un İzoli ve Herdi nahiyelerinde yer alan iskelelerde işlettirilen kayıklar vasıtasıyla ulaşım aksamadan gerçekleştirilmekteydi. Bu kayıklar aynı zamanda bağlı oldukları belediyeler için de önemli gelir kaynaklarıdır. İzoli ve Herdi kayıklarının vergileri (rüsum) Tanzimat’tan itibaren 1890’lı yıllara kadar Malatya belediyesine ait olarak idare edilmiştir. Hâlbuki nehrin bir tarafı merkez vilayet idaresinde (Mamuretü’l-aziz) bulunduğundan bu gelirlerin yarısının da merkez vilayet belediyesinin idaresine bırakılması gerekmekteydi. Bu maksatla Vilayet İdare Meclisi bir karar alarak bu durumun düzeltilmesi talebinde bulunmuştur. Bu çalışmada Osmanlı Arşivi Daire Başkanlığı ŞD-1494-23 noda bulunan belgelerdeki veriler çerçevesinde İzoli ve Herdi kayıkları rüsumunun Malatya belediyesine mi yoksa vilayet merkez belediyesi Mamuretü’l-aziz’e mi ait olduğu konusu aydınlatılmaya çalışılacaktır.
FIRAT NEHRİNDE İŞLETİLEN İZOLİ VE HERDİ KAYIKLARI RÜSUMUNUN HANGİ BELEDİYEYE AİT OLDUĞU MESELESİ